2014
DOI: 10.5897/ajar2013.6760
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Abamectin for the control of root knot nematodes in tobacco seedling production in Zimbabwe

Abstract: The efficacy of different rates of abamectin for the control of root knot nematodes in tobacco soil-based seed beds was evaluated in this study. Different incorporation methods of abamectin in the soil were also evaluated. A combination of 45 ml worked into the soil to a depth of 20 cm using hoes was effective in controlling root knot nematodes. The efficacy was comparable (p = 0.05) to methyl bromide and 1.3 D. The other treatments evaluated did not give control and were comparable to the untreated control. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Similarly, our results regarding growth parameters and juice properties are in conformity with those obtained by [8] and Muzhandu, et al [39] and El-Tanany, et al [6]. They reported that the detected improvement in trees nutrient status followed by B. thuringiensis and abamectin treatment application might be explained by faster absorption of nutrients via the existence of new normal roots.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, our results regarding growth parameters and juice properties are in conformity with those obtained by [8] and Muzhandu, et al [39] and El-Tanany, et al [6]. They reported that the detected improvement in trees nutrient status followed by B. thuringiensis and abamectin treatment application might be explained by faster absorption of nutrients via the existence of new normal roots.…”
Section: Resultssupporting
confidence: 92%
“…It is targeted the δamino-butyric acid in nematode receptors causing increments in the permeability of chloride ions which inally causing death [37]. The effect of abamectin against T. semipenetrans in our study may be attributed to the strong adsorption of abamectin on soil particles which help abamectin to stay in direct contact for more time with the nematode population [38][39][40]. Furthermore, abamectin causes immobility in second stage juveniles (J2) of root knot nematode and this may correlate with a reduction in oxygen uptake [27].…”
Section: Resultsmentioning
confidence: 78%
“…seed treatment controlled root‐knot nematodes (half maximal effective concentration = 0.2 mg a.i. seed –1 ), while Muzhandu (2014) reported similar findings for tobacco seed treatment. Currently, abamectin has a 24(C) registration for use on golf course putting greens in numerous states; however, nematicidal efficacy data are limited, and inconsistent results have been reported in some cases.…”
mentioning
confidence: 56%
“…incognita (Radwan et al, 2019). Moreover, abamectin is adsorbed tightly to soil particles which attributed to the immobility of abamectin molecules in the soil (Lopez-Perez et al, 2011;Muzhandu et al, 2014). On the other hand, oxamyl and ethoprophos are belonging to carbamate and organophosphate groups, respectively, and both are considered AChE inhibitors which inhibited acetylcholinesterase in synaptic zones of the nervous system, thereby disrupt nervous transmission at that location (Corbett et al, 1984).…”
Section: Introductionmentioning
confidence: 99%